Effects of cross protection with mild strains of prsv-w on 'Menina Brasileira' squash - Rezende, Jorge Alberto Marques; Pacheco, Davi Andrade; Iemma, Antonio Francisco (Pesquisa Agropecuaria Brasileira, 1999)
Cross protection with mild strains combined with tolerance was evaluated for control of papaya ringspot virus - type W (PRSV-W) in squash cultivar 'Menina Brasileira'. Tests carried out in the greenhouse showed that plants premunized with PRSV-W-1 and 2 mild strains were protected against infection with a severe strain of the virus. Protection in the field was evaluated comparing plants premunized with the mild strains, plants infected with severe strains and healthy plants exposed to natural infection (control). Protection index was obtained through yield of marketable and non marketable fruits harvested from individual plants. Average yield (weight) of marketable fruits from protected plants was approximately 33% higher than that of naturally infected plants in the field. Combination of mild strain protection and tolerance of 'Menina Brasileira' provided a better disease control with a significant increase of fruit yield.